2016
DOI: 10.1016/j.ifacol.2016.10.267
|View full text |Cite
|
Sign up to set email alerts
|

Geometric tracking control for a nonholonomic system: a spherical robot

Abstract: This paper presents tracking control laws for two different objectives of a nonholonomic system -a spherical robot -using a geometric approach. The first control law addresses orientation tracking using a modified trace potential function. The second law addresses contact position tracking using a right transport map for the angular velocity error. A special case of this is position and reduced orientation stabilization. Both control laws are coordinate free. The performance of the feedback control laws are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…More recently, [13] provides a detailed analysis of the trajectory of the Chaplygin sphere's contact point, and it has been shown that the dynamics of the Chaplygin top exhibit a strange attractor [14] and the phenomenon of reversal [15]. The dynamics of the rolling ball with dynamic internal structure is also an active topic in the nonholonomic mechanics literature [16,17,7,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, [13] provides a detailed analysis of the trajectory of the Chaplygin sphere's contact point, and it has been shown that the dynamics of the Chaplygin top exhibit a strange attractor [14] and the phenomenon of reversal [15]. The dynamics of the rolling ball with dynamic internal structure is also an active topic in the nonholonomic mechanics literature [16,17,7,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Gajbhiye 2016 [30] designed two control laws for spherical robot trajectory tracking that are the orientation tracking using a modified traced potential function and the contact position tracking using transport map. The proposed method claimed to be able to reduced orientation stabilization and demonstrated using simulation.…”
Section: Path Planning and Trajectory Tracking Control Discussionmentioning
confidence: 99%
“…Roozegar et al [47] studied the optimal motion planning and control of a nonholonomic spherical mobile robot by the method of dynamic programming (DP). Gajbhiye and Banavar [48] established the tracking control law of two different targets (spherical robot) in the nonholonomic system. Other control methods were also adopted for the stability control of spherical robot: the nonlinear high order (second order) sliding mode feedback control [49] and a grey PID fuzzy controller [50].…”
Section: Introductionmentioning
confidence: 99%